AB0352 HIGH PREVALENCE OF ANTICIPATORY AND ASSOCIATIVE SYMPTOMS OF METHOTREXATE INTOLERANCE IN PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Tekaya, Rawdha; Triki, Wafa; Tekaya, Aicha Ben; Saidane, Olfa; Mahmoud, Ines; Abdelmoula, Leila; ,
Abstract : Background: Methotrexate (MTX) is the most widely used anti-rheumatic drug in the treatment of Rheumatoid Arthritis (RA) due to low costs, efficacy and an acceptable safety profile. However MTX has certain side effects. The most common side effects include the gastrointestinal tract not only after taking MTX, but also before MTX intake (anticipatory) and when thinking of MTX (associative). Objectives: The aim of this study was to assess the prevalence of MTX intolerance and particularly the anticipatory and associative symptoms using the validated methotrexate intolerance Severity Score (MISS) (1). Methods: We performed a cross-sectional descriptive study that involved patients with RA and treated by MTX for more than 3 months, compiled from Charles Nicolle hospital's rheumatologic department. The tolerance of MTX was assessed by the MISS questionnaire. The MISS Questionnaire includes five elements: abdominal pain, nausea, vomiting, fatigue, and behavioral symptoms of restlessness, crying, irritability and drug refusal. Each symptom is evaluated after intake of MTX, before taking MTX (anticipatory) and on thinking about MTX (associative). MTX intolerance was defined as ≥6 points on the MISS, with at least 1 point on anticipatory, associative or behavioral adverse effects. Results: A total of 100 RA patients (87 women and 13 men) with a mean age of 53, 5 years. The MTX was administrated by oral route in 91% of patients; the other 9% received it by intramuscular way. The average MTX weekly dose was 15, 4mg. The average MTX duration was 76, 7 months. All patients received folic acid with an average of 7, 6 mg a week. MTX intolerance was found in 36% of patients. Abdominal pain was the most common symptom occurring in 55% of patients and up to 91.66% in MTX-intolerant patients, followed by nausea in 51% of patients and in 86.11% of MTX-intolerant patients and vomiting in 16% of patients and in 44.44% of MTX intolerant-patients. Anticipatory and associative abdominal pain affected 72, 2% and 69, 4 of intolerant-patients respectively. Anticipatory and associative nausea were found in 58, 3% and 59% of intolerant-patients respectively. Anticipatory vomiting occurred in 16.6% of intolerant-patients. Overall, behavioral symptoms occurred in 75% of intolerant-patients, of whom 19.4% refused MTX. Older age was significantly correlated with better tolerance to MTX (p=0, 02). There was no correlation between the dose of MTX, the duration of MTX intake and the route of MTX and the MISS score (respectively p=0, 7, p=0, 07and p=0, 2). Also, the use of other disease modifying drugs didn't worsen the tolerance of MTX. Conclusion: To conclude intolerance to MTX is frequently seen in RA. In addition to gastrointestinal symptoms after taking MTX, RA patients can suffer from anticipatory and associative gastrointestinal symptoms. We should screen these symptoms earlier using MISS questionnaire in order to improve MTX compliance. Reference: [1] Bulatovic M, Heijstek MW, Verkaaik M, van Dijkhuizen EH, Armbrust W, Hoppenreijs EP, et al. High prevalence of methotrexate intolerance in juvenile idiopathic arthritis: development and validation of a methotrexate intolerance severity score. Arthritis and rheumatism. 2011;63(7):2007-13. Acknowledgement: None Disclosure of Interests: None declared